2017
DOI: 10.1177/0004867417738055
|View full text |Cite
|
Sign up to set email alerts
|

Treating anxiety and depression in young adults: A randomised controlled trial comparing clinician-guided versus self-guided Internet-delivered cognitive behavioural therapy

Abstract: These results indicate the potential of carefully developed Internet-delivered cognitive behaviour therapy interventions for young adults with anxiety and depression provided in either self or therapist-guided format. Further large-scale research is required to determine the short- and long-term advantages and disadvantages of different models of support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 45 publications
1
45
1
Order By: Relevance
“…While the primary aim of human support is usually to foster greater adherence [ 14 , 45 , 46 ], support did not influence adherence behavior for the participants in this study. While earlier research among clinical cohorts have indicated that supported interventions yielded better adherence and outcomes [ 29 , 47 , 48 ], numerous studies have also shown that human support made no difference [ 31 , 32 , 34 , 49 - 53 ]. Considering the extensive repertoire of previously identified factors affecting adherence, it is plausible that, in this nonclinical group, a wide range of variants may have influenced adherence at the individual level [ 14 ], reducing the potential impact of human support as a single factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the primary aim of human support is usually to foster greater adherence [ 14 , 45 , 46 ], support did not influence adherence behavior for the participants in this study. While earlier research among clinical cohorts have indicated that supported interventions yielded better adherence and outcomes [ 29 , 47 , 48 ], numerous studies have also shown that human support made no difference [ 31 , 32 , 34 , 49 - 53 ]. Considering the extensive repertoire of previously identified factors affecting adherence, it is plausible that, in this nonclinical group, a wide range of variants may have influenced adherence at the individual level [ 14 ], reducing the potential impact of human support as a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent web-based interventions for common mental health disorders, comparing supported and unsupported arms, have found that well-designed self-guided interventions achieve significant improvements in outcomes and maintain high adherence rates irrespective of support provided [ 32 - 34 ]. Notably, in some cases, treatment satisfaction was higher in supported arms [ 34 , 35 ] and some participants perceived support as necessary to success [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants then choose between information to assist with self-management, referral to another service or ICBT. The clinic offers seven ICBT programs that have been validated in clinical trials, including transdiagnostic treatments designed to treat symptoms of anxiety and depression (the Wellbeing, Wellbeing Plus, Mood Mechanic, and Indigenous Wellbeing courses), and disorder-specific treatments for obsessive compulsive disorder, post-traumatic stress disorder, and chronic pain ( Dear et al, 2013 ; Titov et al, 2013 ; Wootton et al, 2013 ; Johnston et al, 2014 ; Spence et al, 2014 ; Wootton et al, 2014 ; Dear et al, 2015 ; Titov et al, 2015b ; Wootton et al, 2015 ; Dear et al, 2016 ; Fogliati et al, 2016 ; Hadjistavropoulos et al, 2016 ; Dear et al, 2017 ). These treatments all comprise five lessons, delivered over eight-weeks.…”
Section: Summary Of the Five Clinicsmentioning
confidence: 99%
“…In this delivery model, referred to as personcentred iCBT, clinician guidance is provided when requested or clinically indicated. Recent trials have supported the provision of optional guidance (Dear et al, 2017;Hadjistavropoulos et al, 2017). While a person-centred iCBT model may be best, based on our findings, the use of translated and minimally monitored transdiagnostic iCBT programs may be an optimal and acceptable first step to increase access to iCBT.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, as mentioned above, the treatment group was younger (31.2 vs 39.6 years). Lower rates of adherence to mental health services have been found among young adults (Collins et al, 2004;Merikangas et al, 2011) including for iCBT (Dear et al, 2017). The efficacy of the French Wellbeing Course against an active treatment group and the generalizability of the findings in routine care remain to be assessed.…”
Section: Discussionmentioning
confidence: 98%